ITER plasma control system final design and preparation for first plasma. (21st September 2021) - Snipes, J.A.; de Vries, P.C.; Gribov, Y.; Henderson, M.A.; Hunt, R.; Loarte, A.; Nunes, I.; Pitts, R.A.; Sinha, J.; Zabeo, L.; Lee, W.-R.; Ambrosino, G.; et al.
Abstract: The ITER plasma control system (PCS) has successfully completed its final design for the first plasma (FP) and engineering operations (EOs) phase and plant system commissioning has begun as ITER prepares for this first operation phase. Commissioning of the essential plant systems will continue as each plant system is completed and made ready for operation. Tokamak assembly has begun with the base and lower cylinder of the cryostat and the lower most poloidal field (PF) coil installed in the tokamak pit. The first vacuum vessel (VV) sector and accompanying two toroidal field (TF) coils are being prepared for transfer to the pit. Once the tokamak is assembled, the cryostat top lid is closed and pump down begins, this will start approximately one year of integrated commissioning (IC) to prepare all of the relevant plant systems for FP operation. After a scheduled one month of plasma operation with the goal of achieving a plasma current > 100 kA for at least 100 ms, there will be about six months of EO to complete commissioning of the superconducting central solenoid, PF, and TF magnet systems to full current, without plasma, to complete this initial ITER operation phase. The PCS final design for FP will be described as well as the IC sequence of the main plant systems required for this operations phase. The plans for the FP operation campaign will be described, including specific challenges present on ITER due to large VV eddy currents, issues associated with electron cyclotron heating (ECH) assist, neutral pressure and impurities. This will be followed by the EO phase to commission full current operation of the superconducting magnets, possibly including plasma operation at full TF of 5.3 T to have improved conditions both for Ohmic plasma initiation and ECH absorption.